(untitled) (GUB Journal of Science and Engineering, 2018)
HelioScope is the solar industry’s leading software platform for designing and analysis performance of a solar plant for a medium to large solar PV plants. Folsom Labs developed HelioScope, an advanced solar PV design software for medium to large solar PV plant. In this paper, the authors have designed a grid tied solar PV based power plant for a sample area of around 20 acre in the district of Rajshahi, Bangladesh. The main feature of the HelioScope software is the efficient layout of the arrays and blocks of the panels once the location of the area is set in the software. Also, authors have tried to focus on the variation of the solar PV output with the variation of the tilt angle of the panels. Normally, in a particular area, tilt angle is adjusted according to the latitude angle of the concerned area. In densely populated countries like Bangladesh, scarcity of land for solar PV generation is extremely acute although there is abundant solar energy available for setting up of solar PV plants. By increasing the tilt angle, substantial area can be saved which can be utilized to set up more numbers of solar panels when compared to the area required with the normal tilt angle which ultimately enhances the generation capacity of the plant and reduce the cost. Solar PV generation for the sample area has been determined for different tilt angles and it has been shown that the solar PV generation increases substantially with the increase of the tilt angle thereby reducing the cost of energy for the sample area under consideration. GUB JOURNAL OF SCIENCE AND ENGINEERING, Vol 5(1), Dec 2018 P 1-5